Javanese Literature and Culture Value in Prosesion of Traditional Ceremony Dhukutan at Nglurah Village, Tawangmangu Regency, Jawa Tengah - Mila Anggar Wati; Sumarwati Sumarwati; Kundharu Saddhono (Hortatori : Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2018)
This article is one of wide studies that analyze literature and cultural values and prosesion in traditional ceremony of Dhukutan at Nglurah Village Tawangmangu Regency. Those traditional ceremony become tourist attractions. This study uses qualititive method inludes collection of primary an secondary sources such as literature study, observation, structured and in-depth interviews. Traditional ceremony have been existed during the ancestor period, it is always accompanied by the presence of ubarampe that has philosophical and historical significance among them. There are five Javanese literature and culture values in Dhukutan; 1) hedonic value, 2) artistic value, 3) cultural value, 4) ethical, moral, religious value, 5) practical value. There are three steps in Dhukutan , 1) preparation, 2) core ceremony, 3) closing . All sesaji in this traditional ceremony using material of corn. The purpose of this study is to knowing Javanese Literature and Culture Value and prosesion of Dhukutan ceremony and oral regulations of Dhukutan.